Complete mitochondrial genome sequence of Hypostomus francisci (Siluriformes: Loricariidae) - Adriana Heloísa Pereira; Susanne Facchin; Anderson Oliveira do Carmo; Daniela Núñez Rodriguez; Leonardo Cardoso Resende; Yan Kalapothakis; Pedro Brandão Dias Ferreira Pinto; Carlos Bernardo Mascarenhas Alves; Cláudio Henrique Zawadzki; Evanguedes Kalapothakis (Mitochondrial DNA. Part B. Resources, 2019)
Hypostomus francisci, commonly known as “cascudo”, is a fish of ecological importance found in the upper São Francisco River, Minas Gerais, Brazil. Here we present the complete mitogenome (mtDNA) of H. francisci. The whole molecule is 16,541 bp long and contains 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and one control region (D-loop). All the PCGs in the H. francisci mtDNA use the standard ATG start codon, except for Cox1, which utilizes GTG. Seven of the 13 PCGs contain TAA stop codons, three contain a TAG, and three contain the incomplete stop codons TA − or T−.